Pengaruh Lingkungan Kerja, Disiplin Kerja dan Stres Kerja Terhadap Kinerja Pegawai Pada Direktorat Jenderal Bina Keuangan Daerah Kementerian Dalam Negeri - Diah Azahra; Erica, Denny; Mabrur Rachmah, Siti (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2024)
Human resource management is included in organizations that focus on human resources. Human resources or human resources are one of the most important parts of a company, especially at the Directorate General of Regional Financial Development of the Ministry of Home Affairs. This research was conducted to determine the effect of the work environment, work discipline and work stress on employee performance. The analytical tool used was Spss29.0 ver.2023, in this study 40 respondents were used as the study population and the research sample technique used was saturated sampling technique, and questionnaires were used as a data collection tool. From validity test and reliability test The variables of work environment, work discipline and work stress are said to be valid because the value of r count > r table and the reliability test results are said to be reliable with the cornbanch alpha value r count 0.494 > r table 0.304. The results of the determination test for the R square value are 0.308 or 30.8% so that the work environment variables work discipline and work stress have an effect of 30.8% on employee performance, the rest are influenced by other variables not examined. The F test shows the value of Fcount, 5,339 > Ftable, 1.92. Therefore, it can be concluded that the work environment, work discipline and work stress have a simultaneous influence on employee performance. Keywords: Work Environment, Work Discipline, Work Stress, Employee Performance.